2017
DOI: 10.1016/j.tox.2017.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific expression of ATP-binding cassette ( Abc ) transporters and cytoprotective genes in mouse choroid plexus

Abstract: The choroid plexus (CP) and blood-brain barrier (BBB) control the movement of several drugs and endogenous compounds between the brain and systemic circulation. The multidrug resistance associated protein (Mrp) efflux transporters form part of these barriers. Several Mrp transporters are positively regulated by the transcription factor nuclear factor erythroid-2-related factor (Nrf2) in liver. The Mrps, Nrf2 and Nrf2-dependent genes are cytoprotective and our aim was to examine basal gender differences in expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Previous transcriptomic studies have also shown that over the period of 6–21 weeks of age the only difference in ABC transporters expression is a very minor increase of MRP1 (p = 0.04; FC = 1.05; supplementary dataset) 29 . Some previous studies in rodents have indicated that ABC-transporter expression at blood-brain and blood-CSF interfaces may be different between sexes 30 . However other transcriptomic studies have established that for both P14 and 6 weeks adult rats there are no statistically significant differences in ABC transporter expression in the brain between male and female animals 29 .…”
Section: Discussionmentioning
confidence: 95%
“…Previous transcriptomic studies have also shown that over the period of 6–21 weeks of age the only difference in ABC transporters expression is a very minor increase of MRP1 (p = 0.04; FC = 1.05; supplementary dataset) 29 . Some previous studies in rodents have indicated that ABC-transporter expression at blood-brain and blood-CSF interfaces may be different between sexes 30 . However other transcriptomic studies have established that for both P14 and 6 weeks adult rats there are no statistically significant differences in ABC transporter expression in the brain between male and female animals 29 .…”
Section: Discussionmentioning
confidence: 95%
“…The ABC-type transporters act as gatekeepers by allowing or limiting the entrance of a wide variety of substrates across cellular membranes (6). A total of 51 ABC transporter genes have been identified and are grouped into seven subfamilies, namely A-G, based on their phylogenetic distance (7).…”
Section: Introductionmentioning
confidence: 99%
“…Higher relative expression of Abcg2, Abcc1, and Slc29a1 in the placentas of female compared with male fetuses was identified at the mRNA level in this model, emphasizing the role of sex in modulating transporter expression. Sex differences in ATP-binding cassette transporter expression have been described elsewhere [30,64], and are well established in adult rodent and human tissues (though not in the placenta), often demonstrating higher transporter expression and activity in females compared with males for rodent efflux transporters including P-gp [65], and Mrps [59,64]. In-vitro modulation of placental transporter expression by sex hormones, such as 17b-estradiol has also been demonstrated for P-gp and Bcrp [66][67][68]; however, findings of sex-differential transporter expression in an in-vivo model of antiretroviral therapy is novel, and in the context of existing research in in-vitro systems, suggests that differences in transporter expression may be influenced by sex differences in fetal endocrine environment.…”
Section: Discussionmentioning
confidence: 99%